On the empirical content of the formal-informal labor market segmentation hypothesis - Ricardo Paes de Barros (Institute for Applied Economic Research (ipea), 2015)
In this paper we pursue three objectives. First, we compare the wage-distributions in the informal and formal sectors for a group of workers employed in the Brazilian Construction Sector. The empirical regularities we encounter are not, however, specific to this particular group of workers. Indeed, similar resulta are also observed for several other homogeneous groups. Second, we investigate how observed differences in means, variances, and quantiles should be interpreted. Finally, we describe three models for the formal-informal segmentation of the labor market, analyse their consistency with the observed regularities, and discuss how these regularities should be interpreted in the context of each individual model. We conclude that the observed regularities are consistent with a wide range of models, although their interpretation varies remarkably depending on the model we are considering.
Keywords: 330